Business network power as a process for enhancing firm performance: A perspective of RAToC - Nilna Muna; Ni Nyoman Kerti Yasa; Ni Wayan Ekawati; I Made Artha Wibawa; Nyoman Sri Subawa (Cogent Business & Management, 2023)
This study aims to bridge the gap in inconsistent findings on the use of social media technology to enhance firm performance through business network power and market entry speed. The original premise of this study is the formulation of business network power, derived from the resource advantage theory of competition, through social media as a primary process that impacts a firm's performance. Data were collected from a sample of 236 owner-managers of small-to-medium craft subsector enterprises in the creative industry in Bali, Indonesia. The results indicate that social media can be a primary trigger for leveraging business network power and strengthening market entry speed and performance. This study has several theoretical and managerial implications.
Keywords: 650; business network power; firm performance; market-entry speed; Social media use; strategic resources